A conceptual business model of e-fashion: harnessing on big data and analytics - Ahmad Dahlan, Abdul Rahman; Azman, Nur Aina; Jamaludeen, Siti Junaidah; Roslan, Nur Izzuana; Idrus Saaidy, Nur Amirina Rosyada (Research Publish Journal, 2017)
The purpose of this paper is to purpose big data CRM to all online fashion market. This idea has the potential to enhance the system at managing customer data and also the process of order. An ordered set of option for customer to buy online. Desire factors like muslimah modern style where found to have impact on the ranking of the factors. The findings are expected to provide useful guidelines to managers while developing advanced system for customer use. Big data is the large amounts of digital data generated continuously by the population of the global that internal several mostly cannot handle the scale of the information. Big data analytics is the process of examining large amount of data. Big data is characterized by dimension of volume, variety, and velocity. There is some well-established data such as big data CRM (Big Data Customer Relationship Management). A mixed method has been used for the research. Examples from secondary sources have been drawn as a part of the literature review which contain about the importance of fashion. Benchmarking to improve the quality of the business which is compared with other e-commerce and successful fashion online.